Scientific trends and emerging topics in youth female soccer: A bibliometric perspective - Mainer-Pardos, E.; Gonzalo-Skok, O.; Nobari, H.; Roso-Moliner, A. (Apunts Sports Medicine, 2025)
Soccer is the most widely played sport worldwide, and women`s participation has grown exponentially through media visibility, institutional support, and increased opportunities. Young female athletes are important for ensuring the sustainable development of the sport. However, no bibliometric analysis has yet focused specifically on youth women`s soccer. This study aims to fill this gap. A comprehensive search was conducted using the Web of Science database to retrieve scientific articles related to youth women`s soccer, analysing titles, abstracts, and keywords without year restrictions. Results show that research in this field has increased steadily, particularly since 2015. Authors such as Stacey Emmonds, research groups in the USA, and journals including the Scandinavian Journal of Medicine and Science in Sports are leading contributions. Key topics include injury prevention, physical performance, and talent development. This study provides an overview of influential authors, countries, journals, and thematic trends, identifying gaps to guide future research and policy development.